O progresso da ciência: uma análise comparativa entre Karl R. Popper e Thomas S. Kuhn - Ignacio, Leonardo Edi (2015)
This study aims to threat the problem of the scientific progress in Karl R. Popper and Thomas S. Kuhn. The scientific progress, before these two authors was taken as cumulative, so, science would grow on the way that it would incorporate new truths to the amount of truths which already was familiar. However, it was from David Hume that this form of progress was called into question, as he noticed that science rested on invalid inductive inferences, and what was thought to be truth in science was actually invalid because the premises of a inductive argument, though true, did not ensure the truth transmitted to the conclusion, once this last one said much more than what was said on the premises. This issue raised by Hume beyond having affected the scientific method, also implied the irrationality of science. It was in order to resolve this issue that the Vienna Circle proposed probability as a way to avoid both problems coming from the inductive method, as to ensure the rational character of science, although still keeping progress as cumulative. Karl R Popper was one of the first to propose a form of progress that was not positive and cumulative, in other words, the goal of science was no longer the check, nor a high probability, but the falsification of theories. Science for Popper, aims the progress and this factor is an essential part which guarantees him the rational and empirical character of scientific theories. While distortion occurred constantly and repeated overthrow of theories we would be progressing, even on a negative way. In order to solve the prior problems, Popper rejects the induction and propose hipotetic-deductive method of proof instead. On the other hand, Thomas Kuhn intended to explain the progress as non-cumulative and rational, because for this philosopher science progresses through scientific revolutions and the successive exchange of paradigms. These revolutions, on the other hand, does not occur by the means that the traditional logic can capture. As a result, this paper intends to argue in favor of Karl R. Popper, trying to demonstrate, on the field of Popper's thought that the philosophy of science Kuhn is not a position that is away from allegedly trying to combat, namely the Circle of Vienna, and while maintaining the discontinuous progress, its main way of demarcating science, that is, paradigms, is still cumulative. We conclude this study observing that the critical method proposed by Popper, although not without its problems, is a more viable alternative to the progress seen as breaking theories than the model of Kuhn, especially by rewarding the scientist more by imagination and daring to do bold conjecture than by blind obedience to a paradigm.